The maternal genetics structure of the Cham-Raglay-Coho-Ma disclosed by whole mitochondrial DNA - Dinh, Huong Thao; Nong, Van Hai; Nguyen, Thuy Duong (Vietnam Journal of Biotechnology, 2025)
Cham, Raglay, Coho, and Ma were native people residing in Central and Southern Vietnam. Their lifestyle and traditional customs revealed the closeness in contact. Here, the mitogenomes of 126 individuals of these four aforementioned groups were analyzed on a molecular level and evaluated the maternal haplogroup architecture. A total of 445 unique variants were screened 6807 times in this dataset, showing a mean variant count of 54.02 ± 3.77 variants per person. Out of 445 unique variants, 88 were present in all individuals, and 137 were shared between at least two populations. The remaining 220 were exclusive to a single population, in which Raglay retained the most (88 variants), and Coho had the least (22 variants). Ma and Coho shared the highest number of unique variants: 163/445 were identified in both. Pair-wise genetic distance was the highest between Raglay and Coho (Fst = 0.13659) and the lowest between Ma and Coho. The maternal haplogroup profile encompassed 30 representatives, stratified into six macro-haplogroups (B, E, F, M, N and R). M, B, and F accounted for 94.45% of the dataset, and the most prevalent branches were B5a1b1 (11.11%), M24b (10.32%), and F1a1a1 (7.94%). The similarities between highlander populations were shown in the macrohaplogroup components, as well as regional features, while the diversity was expressed in unique variants and specific lineages, providing further understanding of the genetic structure of these underrepresented ethnic groups.